Expression of exosomal and cellular microRNAs: as biomarkers for toluene, ethylbenzene, xylene (TEX) exposure - Lim, Jung-hee; Song, Mi-Kyung; Cho, Yoon; Kim, Woong; Han, Sung Ok; Ryu, Jae-Chun (KOREAN SOCIETY TOXICOGENOMICS & TOXICOPROTEOMICS-KSTT, 2016)
Exosomes, small vesicles released by many cells, are associated with various biological processes and they can potentially be used for prognosis and therapy and as biomarkers of health. Thus, they are gaining attention in toxicological and pathological research. miRNA is also considered as a useful tool to predict health risk caused by environmental toxicants. Volatile organic compounds (VOCs), including toluene (T), xylene (X), and ethylbenzene (E), have been reported to be harmful. Although VOCs are prevalent in the environment, the mechanisms underlying their toxicity are not understood. In this study, a microarray analysis identified 50 miRNAs that were differentially expressed in exosomes and cytosols of HL-60 cell line exposed to three VOCs (TEX). A total of 3,355 putative target genes were classified according to the miRWalk 2.0 database. The Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of the putative target genes showed a correlation with biological processes involved in the regulation of myeloid leukocyte differentiation, MAPK signaling pathway, and pathways in cancer. In conclusion, this study describes alterations in miRNA expression profiles in response to exposure to VOCs and related toxicity affected by significantly expressed target genes. Moreover, it illustrates the value of exosomes as diagnostic biomarkers of toxicity.
Keywords: MESSENGER-RNA EXPRESSION; ORGANIC-COMPOUND VOC; OVARIAN-CANCER; HL-60 CELLS; LEUKEMIA; MIRNA; PATHWAY; PROFILE; LINE